Wind-tunnel experiment on aerodynamic characteristics of a runner using a moving-belt system. Issue 1 (31st December 2016) - Inoue, Tatsuya; Okayama, Takafumi; Teraoka, Takahiro; Maeno, Satoshi; Hirata, Katsuya
Abstract: Wind-tunnel experiments are the most effective approaches both to elucidate the flows around runners in track-and-field athletics, and to evaluate their air resistances. In the present study, we develop a moving-belt system, and show its basic performance, such as the distributions of time-mean flow velocity and turbulent intensity above the moving-belt using a hot-wire anemometer. As a result, we have confirmed the effective improvement of the velocity distributions in terms of flow uniformity and turbulence reduction, especially near the moving-belt surface. Following, using this the developed moving-belt system, we investigate the air resistance on a runner in solo running and in duet running. For solo running, we reveal an increase in air resistance of more than 10% in comparison with the conventional result with no moving-belt system. For duet running, we reveal the optimum duet-running formation where a following runner behind a pacemaker experiences small air resistances or strong drafts.